Damage threshold in adult rabbit eyes after scleral cross-linking by riboflavin/blue light application. (October 2015) - Iseli, Hans Peter; Körber, Nicole; Karl, Anett; Koch, Christian; Schuldt, Carsten; Penk, Anja; Liu, Qing; Huster, Daniel; Käs, Josef; Reichenbach, Andreas; Wiedemann, Peter; Francke, Mike
Abstract: Several scleral cross-linking (SXL) methods were suggested to increase the biomechanical stiffness of scleral tissue and therefore, to inhibit axial eye elongation in progressive myopia. In addition to scleral cross-linking and biomechanical effects caused by riboflavin and light irradiation such a treatment might induce tissue damage, dependent on the light intensity used. Therefore, we characterized the damage threshold and mechanical stiffening effect in rabbit eyes after application of riboflavin combined with various blue light intensities. Adult pigmented and albino rabbits were treated with riboflavin (0.5 %) and varying blue light (450 ± 50 nm) dosages from 18 to 780 J/cm 2 (15 to 650 mW/cm 2 for 20 min). Scleral, choroidal and retinal tissue alterations were detected by means of light microscopy, electron microscopy and immunohistochemistry. Biomechanical changes were measured by shear rheology. Blue light dosages of 480 J/cm 2 (400 mW/cm 2 ) and beyond induced pathological changes in ocular tissues; the damage threshold was defined by the light intensities which induced cellular degeneration and/or massive collagen structure changes. At such high dosages, we observed alterations of the collagen structure in scleral tissue, as well as pigment aggregation, internal hemorrhages, and collapsed blood vessels. Additionally, photoreceptor degenerations associated with microglia activation and macroglia cell reactivity in the retina were detected. These pathological alterations were locally restricted to the treated areas. Pigmentation of rabbit eyes did not change the damage threshold after a treatment with riboflavin and blue light but seems to influence the vulnerability for blue light irradiations. Increased biomechanical stiffness of scleral tissue could be achieved with blue light intensities below the characterized damage threshold. We conclude that riboflavin and blue light application increased the biomechanical stiffness of scleral tissue at blue light energy levels below the damage threshold. Therefore, applied blue light intensities below the characterized damage threshold might define a therapeutic blue light tolerance range. Highlights: Successful establishment of riboflavin/blue light scleral cross-linking in an adult rabbit model. Successful increase of biomechanical scleral stiffness after riboflavin/blue light cross-linking. Characterization of a blue light energy dose below the ocular tissue damage threshold. Definition of a blue light tolerance range in rabbits for a possible therapeutic scleral cross-linking approach.